Adapting to the Effects of Climate Change on Inuit Health - Ford, J; Cunsolo Willox, Ashlee; Chatwood, Susan; Furgal, Christopher; Harper, Sherilee; Mauro, Ian; Pearce, T (American Journal of Public Health, 2014)
Climate change will have far-reaching implications for Inuit health. Focusing on adaptation offers a proactive approach for managing climate-related health risks—one that views Inuit populationsasactiveagents in planning and responding at household, community, and regional levels. Adaptation can direct attention to the root causes of climate vulnerability and emphasize the importance of traditional knowledge regarding environmental change and adaptive strategies. An evidence base on adaptation options and processes for Inuit regions is currently lacking, however, thus constraining climate policy development. In this article, we tackled this deficit, drawing upon our understanding of the determinants of health vulnerability to climate change in Canada to propose key considerations for adaptation decision-making in an Inuit context.